2015
DOI: 10.1007/s40688-015-0068-4
|View full text |Cite
|
Sign up to set email alerts
|

Validation and Utility of the Social Emotional Health Survey—Secondary for Japanese Students

Abstract: The article explores the use of the Social and Emotional Health Survey-Secondary version (SEHS-S) with a sample of 975 Japanese students in Grades 7-9 attending schools located northwest of Tokyo. A confirmatory factor analysis using half the sample confirmed the four-factor structure of the SEHS-S, and further analyses verified its secondorder factor model including Belief-in-Self, Belief-in-Others, Emotional Competence, and Engaged Living, all of which contribute to a latent second-order construct labeled Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
26
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 23 publications
10
26
1
2
Order By: Relevance
“…The overall higher-order covitality score was used in this study as a measure of social-emotional wellbeing. Evidence for the higher-order invariance model has been provided across multiple, diverse samples including U.S. (You et al, 2015), Australian (Pennell, Boman, & Mergler, 2015), Korean (Lee, You, & Furlong, 2015), and Japanese (Ito, Smith, You, Shimoda, & Furlong, 2015) samples. For this sample, the internal consistency for the overall covitality score was .88.…”
Section: Methodsmentioning
confidence: 99%
“…The overall higher-order covitality score was used in this study as a measure of social-emotional wellbeing. Evidence for the higher-order invariance model has been provided across multiple, diverse samples including U.S. (You et al, 2015), Australian (Pennell, Boman, & Mergler, 2015), Korean (Lee, You, & Furlong, 2015), and Japanese (Ito, Smith, You, Shimoda, & Furlong, 2015) samples. For this sample, the internal consistency for the overall covitality score was .88.…”
Section: Methodsmentioning
confidence: 99%
“…An increasing number of studies have provided information about the psychometric properties of the SEHS-S, including for the validity of the higher-order model, invariance across sociocultural and gender groups, reliability (internal consistency), and validity evidence (construct, predictive, and convergent, among others). Previous studies reported evidence supporting the reliability and validity of the higher-order measurement model by means of Confirmatory Factor Analyses [15,[17][18][19]. Each study replicated the same higher-order structure with high factor loadings (all in the 0.50-0.91 range).…”
Section: Covitality Psychometric Supportmentioning
confidence: 71%
“…Each study replicated the same higher-order structure with high factor loadings (all in the 0.50-0.91 range). Following from previous CFAs, evidence has supported measurement invariance for gender [15,17,18], younger and older adolescents [19], and five ethnic groups (Latino, White, Asian, Black, and multiethnic) of California students [20].…”
Section: Covitality Psychometric Supportmentioning
confidence: 89%
See 1 more Smart Citation
“…Within the context of a whole school strategy, one important component of school psychologists' efforts has been the development of measures and procedures to monitor students' personal and social assets that are associated with flourishing and thriving development. Ito et al (2015) provide an example of how the Social Emotional Health Survey-Secondary was adapted for use with Japanese students, such efforts are important to achieve the goal of validating well-being related instruments that can be used in research and applied settings cross nationally (Kim et al 2016). Although the development and refinement of well-validated measures is vital, school psychologists also need to know how to use these measures most effectively in support of school-based well-being enhancing initiatives.…”
mentioning
confidence: 99%